Examining the existing knowledge base for enablers of family recovery in mental health: a protocol for a scoping review of national and international literature - Michael John Norton; Kerry Cuskelly; Gina Delaney (BMJ Open)
Introduction Recovery-oriented services in mental health are becoming an accepted approach across much of the globe. While the development of recovery-oriented approaches has focused mainly on people accessing mental health services, families of those accessing services also need to be included under the discussions of mental health recovery within mental health service provision. It is important that service providers understand what support families require in order to facilitate their recovery journeys. To that end, this review will seek to ascertain what evidence exists on the enablers of family recovery from national and international literature.Method and analysis This proposed scoping review aims to investigate the family recovery enablers within a mental health context. A Preferred Reporting Items for Systematic Reviews and Meta-Analysis compliant scoping review is proposed, based on Arksey and O’Malley’s framework. Search terms are stated and a variety of databases (CINAHL, JSTOR, Ovid SP, PsycINFO, PubMed, RCNi, Science Direct, Web of Science and Wiley Online Library) and repositories (Google, Google Scholar and ResearchGate) will be consulted to examine papers based on a predetermined inclusion/exclusion criteria. The search range is from 1 January 2012 to 31 December 2022.Ethics and dissemination As this paper presents a protocol for a scoping review of the literature into family enablers in mental health, no ethical approval is required. The preprint protocol was added to OSF Registries on 29 October 2021 where it is freely available. The registry will be updated once this paper has been published. The resulting scoping review will be distributed through peer-reviewed publication in a high impact journal.